Implementation and Operational Research: Evaluation of Swaziland's Hub-and-Spoke Model for Decentralizing Access to Antiretroviral Therapy Services. (1st May 2015) - Auld, Andrew F.; Kamiru, Harrison; Azih, Charles; Baughman, Andrew L.; Nuwagaba-Biribonwoha, Harriet; Ehrenkranz, Peter; Agolory, Simon; Sahabo, Ruben; Ellerbrock, Tedd V.; Okello, Velephi; Bicego, George
Abstract : Background: In 2007, Swaziland initiated a hub-and-spoke model for decentralizing antiretroviral therapy (ART) access. Decentralization was facilitated through (1) down-referral of stable ART patients from overburdened central facilities (hubs) to primary health care clinics (spokes) and (2) ART initiation at spokes (spoke initiation). Methods: We conducted a nationally representative retrospective cohort study among adult ART enrollees during 2004–2010 to assess the effect of down-referral and spoke-initiation on rates of loss to follow-up (LTFU), death, and attrition (death or LTFU). Sixteen of 31 hubs were randomly selected using probability-proportional-to-size sampling. Seven selected facilities had initiated the hub-and-spoke model by study start. At these facilities, 1149 of 24, 782 hub-initiated and maintained and 878 of 7722 down-referred or spoke-initiated patient records were randomly selected and analyzed. At the 9 hub-only facilities, 483 of 6638 records were randomly selected and analyzed. Multivariable proportional hazards regression was used to assess effect of down-referral (a time-varying covariate) and spoke-initiation on outcomes. Results: At ART initiation, median age was 35, 65% were female, and median CD4 count was 147 cells per microliter. Controlling for known confounders, down-referral was strongly protective against LTFU [adjusted hazard ratio (AHR) 0.38; 95% confidence interval (CI): 0.29 to 0.50] and attrition (AHR = 0.50; 95% CI: 0.34 to 0.76) but not mortality. Compared with hub-initiated and maintained patients, spoke-initiated patients had lower LTFU (AHR 0.59; 95% CI: 0.45 to 0.77) and attrition rates (AHR 0.60; 95% CI: 0.47 to 0.77), but not mortality. Conclusions: Down-referral and spoke-initiation within a hub-and-spoke ART decentralization model were protective against LTFU and overall attrition and could facilitate future ART program expansion. Abstract : Supplemental Digital Content is Available in the Text.